No effect of triheptanoin on exercise performance in McArdle disease. Issue 10 (14th September 2019) - Madsen, Karen L.; Laforêt, Pascal; Buch, Astrid E.; Stemmerik, Mads G.; Ottolenghi, Chris; Hatem, Stéphane N.; Raaschou‐Pedersen, Daniel T.; Poulsen, Nanna S.; Atencio, Maria; Luton, Marie‐Pierre; Ceccaldi, Alexandre; Haller, Ronald G.; et al.
Abstract: Objective: To study if treatment with triheptanoin, a 7‐carbon triglyceride, improves exercise tolerance in patients with McArdle disease. McArdle patients have a complete block in glycogenolysis and glycogen‐dependent expansion of tricarboxylic acid cycle (TCA), which may restrict fat oxidation. We hypothesized that triheptanoin metabolism generates substrates for the TCA, which potentially boosts fat oxidation and improves exercise tolerance in McArdle disease. Methods: Double‐blind, placebo‐controlled, crossover study in patients with McArdle disease completing two treatment periods of 14 days each with a triheptanoin or placebo diet (1 g/kg/day). Primary outcome was change in mean heart rate during 20 min submaximal exercise on a cycle ergometer. Secondary outcomes were change in peak workload and oxygen uptake along with changes in blood metabolites and respiratory quotients. Results: Nineteen of 22 patients completed the trial. Malate levels rose on triheptanoin treatment versus placebo (8.0 ± SD2.3 vs. 5.5 ± SD1.8  µ mol/L, P  < 0.001), but dropped from rest to exercise ( P  < 0.001). There was no difference in exercise heart rates between triheptanoin (120 ± SD16 bpm) and placebo (121 ± SD16 bpm) treatments. Compared with placebo, triheptanoin did not change the submaximal respiratory quotient (0.82 ± SD0.05 vs. 0.84 ± SD0.03), peak workload (105 ± SD38 vs. 102 ± SD31 Watts), or peak oxygen uptake (1938 ± SD499 vs. 1977 ± SD380 mL/min). Interpretation: Despite increased resting plasma malate with triheptanoin, the increase was insufficient to generate a normal TCA turnover during exercise and the treatment has no effect on exercise capacity or oxidative metabolism in patients with McArdle disease.